IMPLIKASI BUDAYA PATRIARKI DALAM KESETARAAN GENDER DI LEMBAGA PENDIDIKAN MADRASAH ( Studi Kasus pada Madrasah di Kota Parepare) - Anwar, Anwar (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2017)
This paper describes the reality of gender equality that occurs in madrasah education institutions. Madrasahs as educational institutions with Islamic heritage have not been able to escape from the pattern of relationships that create gender bias in education systems and planning. Gender terminology is always the basis of consideration to determine the position and role of management and the level of participation in education. It is constructed by at least two main points, namely religious ideology which is the foundation of the ideology of understanding, attitude and behavior about gender equality. Furthermore, religious ideology undergoes a process of assimilation at the cultural level so as to form an elementary view that men have social advantages compared with women.